Small-molecule inhibition of APT1 affects Ras localization and signaling - Dekker, Frank J; Rocks, Oliver; Vartak, Nachiket; Menninger, Sascha; Hedberg, Christian; Balamurugan, Rengarajan; Wetzel, Stefan; Renner, Steffen; Gerauer, Marc; Schölermann, Beate; Rusch, Marion; Kramer, John W; et al. (Nature chemical biology, 2010)
Reversible palmitoylation controls the localization and signaling of Ras. Development of a potent and specific small molecule inhibitor of the thioesterase APT1 reveals that this enzyme depalmitoylates Ras in cells. Inhibition of APT1 led to redistribution and altered activity of HRas, NRas and an oncogenic mutant Ras. Cycles of depalmitoylation and repalmitoylation critically control the steady-state localization and function of various peripheral membrane proteins, such as Ras proto-oncogene products. Interference with acylation using small molecules is a strategy to modulate cellular localization—and thereby unregulated signaling—caused by palmitoylated Ras proteins. We present the knowledge-based development and characterization of a potent inhibitor of acyl protein thioesterase 1 (APT1), a bona fide depalmitoylating enzyme that is, so far, poorly characterized in cells. The inhibitor, palmostatin B, perturbs the cellular acylation cycle at the level of depalmitoylation and thereby causes a loss of the precise steady-state localization of palmitoylated Ras. As a consequence, palmostatin B induces partial phenotypic reversion in oncogenic HRasG12V-transformed fibroblasts. We identify APT1 as one of the thioesterases in the acylation cycle and show that this protein is a cellular target of the inhibitor.